The Avaliator : uma ferramenta web para avaliação de qualidade de código-fonte de aprendizes de programação em Python - Resende, Erick Santos (2024)
One of the challenges faced by programming educators is the difficulty of grading source code and objectively assessing its quality. In response to this, a tool was developed in 2021 that compares source code from both teachers and students, subsequently determining its quality based on predefined metrics. However, the tool lacked a user-friendly interface, complicating the evaluation process and making it cumbersome as it required manual saving of student and teacher source codes. This project focuses on the development of a web application that evaluates source code using this tool, in conjunction with a connection to the online judge The Huxley to automatically access exercise and submission data on the platform. The developed tool provides programming educators who already use The Huxley in their teaching practices with a source code scoring system, aiding them in identifying each student’s strengths and weaknesses. The tool enables the detection of solutions with metrics that are better or worse than those of the teacher, allowing the analysis of reasons for such divergences and facilitating direct communication with the student regarding specific solutions.